Galeaclolusite, [Al6(AsO4)3(OH)9(H2O)4]⋅8H2O, a new bulachite-related mineral from Cap Garonne, France. (4th April 2021) - Grey, Ian E.; Favreau, George; Mills, Stuart J.; Mumme, W. Gus; Bougerol, Catherine; Brand, Helen E.A.; Kampf, Anthony R.; MacRae, Colin M.; Shanks, Finlay
Abstract: Galeaclolusite, [Al6 (AsO4 )3 (OH)9 (H2 O)4 ]⋅8H2 O, is a new secondary hydrated aluminium arsenate mineral from Cap Garonne, Var, France. It forms crusts and spheroids of white fibres up to 50 μm long by 0.4 μm wide and only 0.1 μm thick. The fibres are elongated along [001] and flattened on (100). The calculated density is 2.27 g⋅cm –3 . Optically, galeaclolusite is biaxial with α = 1.550(5), β not determined, γ = 1.570(5) (white light) and partial orientation: Z = c (fibre axis). Electron microprobe analyses coupled with crystal structure refinement results gives an empirical formula based on 33 O atoms of Al5.72 Si0.08 As2.88 O33 H34.12 . Galeaclolusite is orthorhombic, Pnma, with a = 19.855(4), b = 17.6933(11), c = 7.7799(5) Å, V = 2733.0(7) Å 3 and Z = 4. The crystal structure of galeaclolusite was established from its close relationship to bulachite and refined using synchrotron powder X-ray diffraction data. It is based on heteropolyhedral layers, parallel to (100), of composition Al6 (AsO4 )3 (OH)9 (H2 O)4 and with H-bonded H2 O between the layers. The layers contain [001] spiral chains of edge-shared octahedra, decorated with corner-connected AsO4 tetrahedra, that are the same as in the mineral liskeardite.